La relazione a distanza tra corpo e tecnologia digitale - Medici, Caterina (Il sogno della farfalla, 2021)
In this paper the author comments on an editorial article written by the children and adolescent psychiatrist Massimo Ammaniti. In this editorial the specialist affirms to be wary worried about human interactions through technology. These considerations are somehow based on evolutionistic ideas and Freudian conceptions of corporeality. In this sense the psychiatrist affirms that socia networks are responsible for a decline in empathy among young people. Ammaniti’s statements are thoroughly commented in the attempt to analyse the underlying cultural ideas, characterized by a sense of prejudice against technological innovation and at the same time by the idea that human beings naturally lack of affection. In contrast with this analysis the author proposes a vision of human relationships based on the capacity of an affective presence.